Spatially Organized Aggregation of Misfolded Proteins as Cellular Stress Defense Strategy - Miller, Stephanie Barbara Maria; Mogk, Axel; Bukau, Bernd (Journal of molecular biology, 2015)
An evolutionary conserved response of cells to proteotoxic stress is the organized sequestration of misfolded proteins into subcellular deposition sites. In Saccharomyces cerevisiae, three major sequestration sites for misfolded proteins exist, IPOD (insoluble protein deposit), INQ (intranuclear quality control compartment) [former JUNQ (juxtanuclear quality control compartment)] and CytoQ. IPOD is perivacuolar and predominantly sequesters amyloidogenic proteins. INQ and CytoQs are stress-induced deposits for misfolded proteins residing in the nucleus and the cytosol, respectively, and requiring cell-compartment-specific aggregases, nuclear Btn2 and cytosolic Hsp42 for formation. The organized aggregation of misfolded proteins is proposed to serve several purposes collectively increasing cellular fitness and survival under proteotoxic stress. These include (i) shielding of cellular processes from interference by toxic protein conformers, (ii) reducing the substrate burden for protein quality control systems upon immediate stress, (iii) orchestrating chaperone and protease functions for efficient repair or degradation of damaged proteins [this involves initial extraction of aggregated molecules via the Hsp70/Hsp104 bi-chaperone system followed by either refolding or proteasomal degradation or removal of entire aggregates by selective autophagy (aggrephagy) involving the adaptor protein Cue5] and (iv) enabling asymmetric retention of protein aggregates during cell division, thereby allowing for damage clearance in daughter cells. Regulated protein aggregation thus serves cytoprotective functions vital for the maintenance of cell integrity and survival even under adverse stress conditions and during aging.
Gesehen am 08.06.2020